2022
DOI: 10.21037/jtd-22-1261
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA KCNQ1OT1 enhances the radioresistance of lung squamous cell carcinoma by targeting the miR-491-5p/TPX2-RNF2 axis

Abstract: Background: Lung cancer, especially lung squamous cell carcinoma (LUSC), is one of the most common malignant tumors worldwide. Currently, radiosensitization research is a vital direction for the improvement of LUSC therapy. Long non-coding RNAs (lncRNAs) can be novel biomarkers due to their multiple functions in cancers. However, the function and mechanism of lncRNA KCNQ1OT1 in the radioresistance of LUSC remain to be elucidated. Methods:The clonogenic assay was employed to determine the radioresistance of SK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In the past decade, extensive studies have identified many types of lncRNAs that can serve as promising biomarkers for cancer diagnosis and targeted therapy. For instance, LINC01608 has been identified as a promising prognostic biomarker for hepatocellular carcinoma ( Liu et al, 2022 ), NALT1 promotes the targeting of PEG10 via sponge microRNA-574-5p to advance colorectal cancer progression ( Ye et al, 2022 ), and RNA demethylase ALKBH5 promotes lung cancer progression ( Shen et al, 2022 ). However, traditional biological experiments used to identify the association between lncRNA and diseases, such as PCR ( Heid et al, 1996 ) and microarray analysis ( Zhai et al, 2015 ), have always been limited by high costs and lack of specificity in exploring and understanding lncRNA.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, extensive studies have identified many types of lncRNAs that can serve as promising biomarkers for cancer diagnosis and targeted therapy. For instance, LINC01608 has been identified as a promising prognostic biomarker for hepatocellular carcinoma ( Liu et al, 2022 ), NALT1 promotes the targeting of PEG10 via sponge microRNA-574-5p to advance colorectal cancer progression ( Ye et al, 2022 ), and RNA demethylase ALKBH5 promotes lung cancer progression ( Shen et al, 2022 ). However, traditional biological experiments used to identify the association between lncRNA and diseases, such as PCR ( Heid et al, 1996 ) and microarray analysis ( Zhai et al, 2015 ), have always been limited by high costs and lack of specificity in exploring and understanding lncRNA.…”
Section: Introductionmentioning
confidence: 99%
“…The change of immune status in pro- and anti-tumor immune cells can also affect RT sensitivity ( 14 ). LncRNA KCNQ1OT1 has been clarified as a therapeutic target to improve RT sensitivity ( 15 ). It is becoming increasingly clear that reversing tumor resistance to RT can dramatically improve the efficacy of tumor-targeting RT.…”
Section: Introductionmentioning
confidence: 99%